Increased histone H3 acetylation inhibit the inflammatory response and activate the serum immunity of Pearl oyster Pinctada fucata martensii - Yang, Jingmiao; Yang, Shuai; Liao, Yongshan; Deng, Yuewen; Jiao, Yu (Frontiers in Marine Science, 2023)
To produce cultured pearls, a mantle graft with a nucleus is transplanted into a host pearl oyster, this process is called “transplantation”. The immune response of pearl oyster after transplantation is a major factor that leads to nucleus rejection and death. Butyrate is a histone deacetylase (HDAC) inhibitor which can inhibit the deacetylation process of histones and effectively reduce the inflammatory response. To clarify the function of histone acetylation in immune response after transplantation, butyrate (10 mmol/L) was used for the treatment of pearl oysters before transplantation. Results showed that the proportion of histone H3 acetylation of the hemocytes was significantly increased after butyrate treatment before transplantation (BH group) compared with the control group at 6–24 h. Transcriptome analysis showed that butyrate treatment activated the “lysosome”, inhibited cell migration and cell proliferation at 6 and 12 h, respectively, and activated the intracellular immune recognition response of pearl oyster at 24 h after transplantation. The apoptosis detection revealed no significant difference in the proportion of apoptotic cells between the control and BH group. Moreover, butyrate treatment increased the activity of some immune-related enzymes in the serum of pearl oyster after transplantation.